Pengetahuan Ibu Hamil tentang Terapi Komplementer dalam Persiapan Laktasi - Nurbaiti, Nurbaiti; Gustina, Gustina (3031-8572, 2024)
Mother's milk contains high levels of nutrients which are very beneficial for the health and development of babies in order to achieve optimal growth. Exclusive breastfeeding coverage in Indonesia in 2021 is 56.9%. Exclusive breastfeeding coverage in Jambi Province is 63.3%, however there are still mothers who do not breastfeed exclusively because they experience obstacles in breastfeeding their babies exclusively, these obstacles include work. , mothers feel they are not producing enough breast milk, tired, and breast milk is not flowing smoothly, successful breastfeeding is very important to improve the health of mother and baby. This study aims to determine pregnant women's knowledge about complementary therapies in preparation for lactation. This research was conducted at the Putri Ayu Community Health Center in November 2023 - August 2024, the population of this study were all 32 pregnant women who came to the pregnant women's class, sampling using the technique total sampling, iThe instrument used is a questionnaire, data collection uses primary data and secondary data, data processing consists of editing, coding, scoring, entry dan cleaning then analyzed univariately. The research results showed that the majority of pregnant women's age was 20-35 years (62.5%), the educational level of most pregnant women had a high school education (54%), the mother's occupation was a housewife (65.6%). Pregnant women's knowledge about yoga is good (81%), knowledge about acupressure is quite good (53%), knowledge about aromatherapy is good (81.25%), knowledge about Hypnobreasfeeding quite good (75%). It is hoped that pregnant women can prepare for lactation well, such as seeking information and participating in educational activities provided by health workers, especially regarding preparation for lactation.